2023
DOI: 10.2196/41528
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Integration of Electronic Health Records in Medical Consortiums: Dynamic Modeling Approach Based on the Evolutionary Game Theory

Abstract: Background China has continuously issued policies to speed up the interconnection, mutual recognition, sharing of medical information systems, and data integration management across regions and institutions. However, the vertical integration of electronic health records (EHRs) within the medical consortium is hampered by “poor mechanism and insufficient motivation” and the phenomenon of “free riding” among participating medical institutions, which makes the integration less effective. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The amount of shared costs invested is closely related to the hospital's effort, which can be characterized by the effort level. The effort level can be expressed as 1 2 βM 2 (26), where β represents the cost coefficient of hospital investment, and M represents the hospital's earnings level (benefit level). There are also certain risks for hospitals in the EHR integration.…”
Section: Basic Incentive Model Construction Cost Function Of Hospitalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of shared costs invested is closely related to the hospital's effort, which can be characterized by the effort level. The effort level can be expressed as 1 2 βM 2 (26), where β represents the cost coefficient of hospital investment, and M represents the hospital's earnings level (benefit level). There are also certain risks for hospitals in the EHR integration.…”
Section: Basic Incentive Model Construction Cost Function Of Hospitalsmentioning
confidence: 99%
“…These potential risks may include reduced revenues due to interoperability of test results, and patients loss due to convenient access to medical care. Such potential risk cost can be expressed as 1 2 γ a 2 δ 2 (27). Where γ denotes the risk avoidance intensity of the hospital, determined by the risk awareness of the hospital's decision-making level.…”
Section: Basic Incentive Model Construction Cost Function Of Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different groups may exhibit different adoption behaviors towards particular technologies. Nevertheless, it is essential to note that there is some technology exchange and information communication between leading and subordinate hospitals within medical consortiums [ 28 30 ], which is not equivalent to two utterly independent medical institutions. Furthermore, since some appropriate health technologies that should be widely promoted have only been applied in leading hospitals but are far from widespread in subordinate hospitals [ 6 ], it is necessary to investigate the differences in influencing mechanisms of clinicians’ technology utilization behavior across different levels of hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously reported on the status of China’s MCs reform ( 8 ), regional practical experiences ( 12 ), theoretical frameworks ( 13 ), and development pathways ( 14 ). Although some studies have examined the effects of MCs policy using quantitative analyses, most of them have been conducted from a single perspective, such as assessing inpatient numbers ( 15 ), hospitalization rates ( 16 ), hospitalization expenses ( 17 ), physician flows ( 18 ), informatization construction ( 19 ), and health professionals’ views and satisfaction with regard to MCs reform ( 20 ). For example, Özkaytan et al ( 21 ) found that integrated care models could address complicated healthcare needs and enhance service continuity and coordination.…”
Section: Introductionmentioning
confidence: 99%